ANALISIS SOAL UJIAN AKHIR SEKOLAH BERSTANDAR NASIONAL MATA PELAJARAN BAHASA INDONESIA DI PROVINSI RIAU - Adrilla, Elsa; Hermandra, Hermandra; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe school final test standard questionnaire subject Indonesian national aimed at for students as activity measurement and assessment competence of students nationally. A matter containing question or command that must be answered student with the end result of the value. In question are the sentence as information that is ordered. The sentence that used to be effective sentence. The data analysis technique used are by reading question shuttle, identify useful containing word and sentence are not effective, moving into analizing the data which contains the effective sentence and sentence are not effective, explain sentence contains effective sentence and sentence are not effective to find, and finally, summarizing the element of the identity sentence contains effective sentence and sentence are not effective the national standard school final examination subjects in the Indonesian province of Riau. This research is aimed to express, describe, and analyze the data which contains the sentence effective and sentence are not effective the national standard school final examination subjects in the Indonesian province of Riau. Based on the research conducted, the authors conclude that the sentence about the national standard school final examination subjects in the Indonesian province of Riau sentence are not effective. This study can be used as teaching material development in the world of education especially in the field of language and literature particularly effective use of sentences.Key words: analysis, The school final test standard questionnaire subject Indonesian national, province of Riau.